Herbicide resistant Jungle rice in soybean growing belts of Madhya Pradesh - Chander, Subhash; Tyagi, Vikas C; Ghosh, Dibakar; Chethan, C R; Mishra, Subhash K; Kumar, Bhumesh; Singh, P K (Indian Farming, 2020)
The problems of herbicide resistance in E. colona were observed in Madhya Pradesh. The survey was conducted to collect biotypes of E. colona from different districts of Madhya Pradesh. Thirty-six E. colona biotypes were found resistant against imazethapyr at 4-times of recommended dose. The possible way to manage the herbicide resistant weeds is by adopting the integrated means of weed management.